Hoarding Disorder: A Review - Bárbara Perdigão Stumpf; Cláudia Hara; Fábio Lopes Rocha (Brazilian Society of Geriatrics and Gerontology, 2024)
Hoarding disorder can be defined as a persistent difficulty in discarding items, due to distress associated with such disposal or a perceived need to save items regardless of their actual value. Such behavior must result in the accumulation of clutter, which significantly compromises living conditions, causing distress and/or functional impairment. The most frequently hoarded items are objects and animals. The point prevalence of clinically significant hoarding was estimated to be 1.5 to 2.1% in the general population, and may exceed 6% in the elderly. HD poses a range of health and safety hazards to individuals, especially older adults, generating significant costs to society. The diagnosis of HD is clinical, and should only be established after general medical conditions and other mental disorders that can lead to accumulating behavior have been ruled out. HD appears to follow a chronic, progressive course, and is commonly associated with psychiatric comorbidities. Studies indicate that genetic, familial, cognitive, and traumatic factors are implicated in the etiology of HD. To date, psychotherapies have been the most widely studied therapeutic approaches, but the results of these studies show small effects. Research into pharmacological approaches to HD is still incipient, precluding any conclusions of efficac.